Study of the Average Ion Mass of the Dayside Magnetospheric Plasma. Issue 10 (10th October 2022) - Del Corpo, Alfredo; Vellante, Massimo; Zhelavskaya, Irina S.; Shprits, Yuri Y.; Heilig, Balázs; Reda, Jan; Pietropaolo, Ermanno; Lichtenberger, János
Abstract: The investigation of heavy ions dynamics and properties in the Earth's magnetosphere is still an important field of research as they play an important role in several space weather aspects. We present a statistical survey of the average ion mass in the dayside magnetosphere made comparing plasma mass density with electron number density measurements and focusing on both spatial and geomagnetic activity dependence. Field line resonance frequency observations across the European quasi‐Meridional Magnetometer Array, are used to infer the equatorial plasma mass density in the range of magnetic L ‐shells 1.6–6.2. The electron number density is derived from local electric field measurements made on Van Allen Probes using the Neural‐network‐based Upper‐hybrid Resonance Determination algorithm. The analysis is conducted separately for the plasmasphere and the plasmatrough during favorable periods for which both the plasma parameters are observed simultaneously. We found that throughout the plasmasphere the average ion mass is ≃1 amu for a wide range of geomagnetic activity conditions, suggesting that the plasma mainly consist of hydrogen ions, without regard to the level of geomagnetic activity. Conversely, the plasmatrough is characterized by a variable composition, highlighting a heavy ion mass loading that increases with increasing levels of geomagnetic disturbance. During the most disturbed conditions, the average radial structure shows a broad maximum around 3–4 Earth radii, probably correlated with the accumulation of oxygen ions near the plasmapause. Those ions are mostly observed in the post‐dawn and pre‐dusk longitudinal sectors. Plain Language Summary: The space surrounding the Earth is permeated by plasma whose composition could affect the space weather conditions. The near Earth region, the plasmasphere, roughly co‐rotates with our planet, while the external part, the plasmatrough, streams toward the Sun direction. The solar wind conditions determine the level of the geomagnetic activity and eventually the radial position of the layer separating the plasmasphere from the plasmatrough. We investigate the average ion mass in the dayside region between 1.6 and 6 Earth Radii, using ground based magnetic field observations recorded at the European quasi‐Meridional Magnetometer Array and plasma waves measurements made on Van Allen Probes spacecrafts. The analysis shows that the plasmasphere is practically insensitive to the level of geomagnetic activity being composed predominantly by hydrogen ions. Contrarily, the contribution of oxygen ions in the plasmatrough increases with increasing geomagnetic activity and maximizes between 3 and 4 Earth radii and in the dawn and dusk longitudinal sectors. Key Points: The plasmasphere mainly consists of hydrogen ions for a wide range of geomagnetic activity conditions The contribution of heavy ions in the plasmatrough increases as the geomagnetic activity increases, predominantly close to the plasmapause The highest ion mass loading in the plasmatrough is observed in the longitudinal sectors 7–9 and 15–17 MLT